Combined use of a femtosecond laser and a microkeratome in obtaining thin grafts for Descemet stripping automated endothelial keratoplasty: an eye bank study - Murta, JN (2013)
Purpose: To evaluate the use of a femtosecond laser combined with a microkeratome in the preparation of posterior corneal disks for Descemet stripping automated endothelial keratoplasty (DSAEK). Methods: This experimental study involved ultrathin DSAEK tissue preparation of 22 donor corneas unsuitable for transplantation. The first cut was performed with an Intralase® FS60 laser and the second cut with a Moria CBm 300-µm microkeratome. The thickness of the first cut was modified for each cornea to obtain a final graft thickness of less than 110 µm. Precut and postcut central pachymetry were performed with an ultrasonic pachymeter. Central endothelial cell density (ECD) was calculated before and 24 hours after tissue preparation.  Results: Final graft thickness was 105.0 ± 26.1 (SD) µm (range 65-117). The mean microkeratome head cut thickness was 324.5 ± 10.9 µm (range 310-345). Precut and postcut ECDs averaged  2250 ± 222 and 2093 ± 286 cells/mm2, respectively, representing 6.9% of cell loss. No corneas were perforated. Conclusion: Femtosecond FS60 lasers and Moria CBm 300-µm microkeratomes can be used sequentially to prepare consistently thin DSAEK grafts with no irregular cuts or cornea perforations.